2015
DOI: 10.1007/s11240-015-0762-y
|View full text |Cite
|
Sign up to set email alerts
|

Fungal elicitor-mediated enhancement in phenylpropanoid and naphtodianthrone contents of Hypericum perforatum L. cell cultures

Abstract: Hypericum perforatum cell suspensions were evaluated for their growth, phenylpropanoid and naphtodianthrone productions, and antioxidant activity after treatments with fungal elicitors Fusarium oxysporum, Phoma exigua and Botrytis cinerea. Elicited cells displayed a reduced biomass production, a rapid stimulation of secondary metabolites production and a modification of cell redox state compared to control. Cells responded strongly towards the applied elicitors through the enhanced production of naphtodianthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 58 publications
1
27
0
1
Order By: Relevance
“…Mendhulkar and Vakil (2013) hypothesized the elicitation mechanism as the binding of the elicitor to plasma membrane receptors, which initiates signaling processes that activate plant defense. Fungal elicitors have been widely used to increase the accumulation of natural products in plant cell cultures, and this strategy has been effective in stimulating the production of many chemical classes of secondary metabolites such as alkaloids (Taha et al, 2009), phenolics, flavonoids, anthocyanins Gadzovska et al, 2015), and glucosides (Nadeem et al, 2018). In the present study, the A. niger extract was found to be useful for the enhancement of ephedrine accumulation.…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…Mendhulkar and Vakil (2013) hypothesized the elicitation mechanism as the binding of the elicitor to plasma membrane receptors, which initiates signaling processes that activate plant defense. Fungal elicitors have been widely used to increase the accumulation of natural products in plant cell cultures, and this strategy has been effective in stimulating the production of many chemical classes of secondary metabolites such as alkaloids (Taha et al, 2009), phenolics, flavonoids, anthocyanins Gadzovska et al, 2015), and glucosides (Nadeem et al, 2018). In the present study, the A. niger extract was found to be useful for the enhancement of ephedrine accumulation.…”
Section: Resultsmentioning
confidence: 54%
“…Mendhulkar and Vakil (2013) also reported a significant increase in flavonoid accumulation in suspension cultures of Andrographis paniculata after elicitation with an A. niger extract. Moreover, Gadzovska et al (2015) observed a significant increase in naphtodianthrones, total phenolics, flavonoids, and anthocyanins in Hypericum perforatum cell suspensions treated with A. niger extract. However, as reported in the present study, increasing the concentration of A. niger extract showed less ephedrine accumulation.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations